EEE student mortality-performance analysis. - Denoga, Gay Marie C. (Philippine Engineering Journal)
This is a study of student performance/mortality in the EEE curriculum for the UP EEE Classes of 1990 to 1996 based on student grades in the DEEERS database incurred within the time frame from 1991-1997 using Digital Signal Processing techniques, for the purpose of obtaining a measure of, and predicting a student's course completion capability.